Resistance is fertile: Toward a political ecology of translocal resistance - Bobby Banerjee, Subhabrata; Maher, Rajiv; Krämer, Romy (Organization (London, England), 2023)
There are more than 3000 ongoing conflicts involving the extractive industries (mining, gas, and oil) and communities impacted by extractive activity. Most of these conflicts are in the developing countries of Africa, Asia, and Latin America. In this paper we examine three resistance movements in Brazil, Chile, and India where Indigenous groups are resisting mining operations on their lands. We argue these movements represent forms of translocal subaltern resistance based on local political ecologies of marginalized communities. In particular, we develop the notion of disembeddedness to show how conflicts arise between local political ecologies and the political economy of resource extraction. We contribute to the literature by (1) bridging insights from subaltern studies and political ecology to explain how forms of resistance emerge (2) providing empirical support to theories of translocal resistance by conducting a comparative analysis of resistance movements from three countries. We discuss the theoretical implications of our findings for resistance movements.